Water Resources Management in the Islamic Economics Perspective - Atwal Arifin; Mujiyati Mujiyati; Noer Nasongko; Muhammad Sholahuddin (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Islamic Economic Principles prevent damage and realize the benefit that is maintained for humanity, nature and the environment. This paper presents literature and empirical studies regarding the management of water resources in an Islamic perspective. Literature study is divided into three main sections. The first part is a preliminary study of the concept of water resources management between the Islamic economic system and the conventional economic system. The second presents a discussion of optimizing water resources to meet community and environmental needs and increase village and regional income. The third part that have been carried out regarding the management of water resources in Indonesia. The method used in this study the literature review method, analyzed by content analysis supported by NVivo software. The results of the study are that there an equation but it is a fundamental difference in water resources in the conventional economy compared to the Islamic economy. Besides that, the management of water resources using the Village Owned Enterprise (VOE) model is able to optimize the management of water resources for many people. There is still little review of water resources in the perspective of Islamic Economics. Therefore, an in-depth study is needed to find the VOE success factor model in air resources management in Klaten as well as efforts to find an air resource management model with an Islamic Economics perspective.